Rhetoric, ethic, and moral persuasion in biblical discourse: essays from the 2002 Heidelberg conference - Olbricht, Thomas H.; Eriksson, Anders (Emory studies in early Christianity, 2005)
Keynote address -- Old Testament -- Gospels -- General -- Pauline general -- Pauline Epistles -- Hebrews -- Concluding address